A Study of Comfort Properties Between Various Brand of Face Masks for Malaysian Consumers - Nasaie Zainuddin; Najua Tulos; Syaiful Osman; Muhammad Hisyam Zakaria; Asliza Aris (International Journal of Integrated Engineering, 2024)
Comfort properties refer to the human’s impressions after touching an object. The aim of this study is to identify the comfortability properties of knitted face masks from different brands. Comfort refers to a human’s impressions after touching an object. Three brands were chosen to test the comfort properties, and physical testing was done to identify the characteristics of each brand. Then the samples from three brands were evaluated for breathability and absorbency to achieve the first objective of this study. The brand that offers low breathing resistance is Brand B. Therefore, consumers who have difficulty breathing will feel comfortable since the water vapour that comes out during the inhale and exhale processes can pass through the mask and not trap inside it. Next, for absorbency properties, it can be concluded that the brand C provides the best comfort in terms of absorbency. As a result, the consumer feels comfortable using it because it quickly absorbs moisture from both the outside and inside of the face mask, preventing accumulation.